An efficient approach for superconducting joint of YBCO coated conductors. (1st July 2022) - Huang, Daxing; Shang, Hongjing; Xie, Bowei; Zou, Qi; Dong, Hao; Wang, Kai; Zhang, Lin; Gu, Hongwei; Ding, Fazhu
Abstract: Superconducting joints are crucial for second generation high-temperature superconducting (2G HTS) closed-loop coils that work in the persistent current mode (PCM) operation. Here, we report an efficient approach for superconducting joints of YBa2 Cu3 O7- σ (YBCO) coated conductors (CCs). The YBCO layer is etched to and from some microchannels, which serve as oxygen diffusion paths during oxygenation annealing (OA), to accelerate the recovery of critical current ( I c ) of the joined two YBCO layers. The I c of the superconducting joint is 118 A at 77 K with an optimized joining temperature and a short OA time (10 h), which is about 82% I c of the joined YBCO CCs. The persistent field decay of the closed-loop coil shows a joint resistance ( R j ) of less than 2.2 × 10 −13 Ω at 77 K. Two YBCO films epitaxially grown along the c -axis diffuse into each other at the interface and form a dense joining, enabling superconducting current path. This superconducting joint technique can promote the achievement of the PCM operation in 2G HTS magnet applications, such as magnetic resonance imaging and nuclear magnetic resonance.